Raman Spectroscopy of an Atypical C15‑E,syn Bilin Chromophore in Cyanobacteriochrome RcaE - Okuda, Yuji; Miyoshi, Risako; Kamo, Takanari; Fujisawa, Tomotsumi; Nagae, Takayuki; Mishima, Masaki; Eki, Toshihiko; Hirose, Yuu; Unno, Masashi (The journal of physical chemistry. B, 2022)
Cyanobacteriochromes (CBCRs) belong to the phytochrome superfamily of photoreceptors, the members of which utilize a linear tetrapyrrole (bilin) as a chromophore. RcaE is a representative member of a green/red-type CBCR subfamily that photoconverts between a green-absorbing dark state and red-absorbing photoproduct (Pr). Our recent crystallographic study showed that the phycocyanobilin (PCB) chromophore of RcaE adopts a unique C15-E,syn configuration in the Pr state, unlike the typical C15-E,anti configuration for the phytochromes and other CBCRs. Here, we measured Raman spectra of the Pr state of RcaE with 1064 nm excitation and explored the structure of PCB and its interacting residues under physiologically relevant aqueous conditions. We also performed measurements of RcaE in D2O as well as the sample reconstituted with the PCB labeled with 15N or with both 13C and 15N. The observed Raman spectra were analyzed by quantum mechanics/molecular mechanics (QM/MM) calculations together with molecular dynamics simulations. The Raman spectra and their isotope effects were well-reproduced by the simulated spectra of fully protonated PCB with the C15-E,syn configuration and allowed us to assign most of the observed bands. The present vibrational analysis of the all syn bilin chromophore using the QM/MM method will advance future studies on CBCRs and the related proteins by vibrational spectroscopy.